Implementation of Nearest Neighbor Retrieval - Reddy, SP; Govindarajulu, P (International Journal of Computer Sciences and Engineering, 2025)
Conventional pensiveness queries, like contrast search and nearby neighbor retrieval involve completely on conditions imposed on objects of geometric properties. Nowadays, various applications absorb new types of queries that aspire to hunt out objects satisfying every generalization predicate and a predicate on connected texts. as Associate in Nursing example, instead of considering all the restaurants, a nearest neighbor question would instead elicit the edifice that is the utmost among those whose menu contain “steak, spaghetti, sprite” all at a similar time. Presently the foremost effective resolution to such queries is based on the IR2-tree, which, as shown throughout this paper, aims at a couple of deficiencies that seriously impact its efficiency. motivated by this, we have a tendency to tend to develop a replacement access methodology called the abstraction inverted index with the intention of extends the quality inverted index to deal with flat data, and comes with algorithms that will answer nearby neighbor queries through keywords in real time. As verified by experiments, the projected techniques outgo the IR2-tree and are subjected to significantly, generally by a component of, orders of magnitude.